PERANAN PONDOK PESANTREN DALAM MEMBENTUK KARAKTER SANTRI - Robiatul Adawiyah, Dinda; Safina Salma, Raisha; Naflah Solehati, Maudy; Apip, Moch; Masruri, Ahmad; Munali, Munali (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2025)
The purpose of the study was to measure the role of Islamic boarding schools in the character building of students with three dimensions, namely: character education, encouragement of character building, and self-character building. The research methodology used qualitative research with a case study research approach with a sample size of 75 students selected by random sampling. Data were collected through interviews and analyzed using percentage score formulation. Research results: 1) the lowest percentage score is in the dimension of forming one's own character in question 14 at 92%. The score of 92% can be categorized that students have been able to apply good manners in the boarding school and 2) the second lowest score is in the dimension of character education on items 3 and 7 at 95%. A score of 95% can be categorized as the rules at the boarding school make students more disciplined and character building can be through extracurricular activities. The average percentage of the three dimensions is 98%. The 98% score can be concluded that the character building of students can be categorized as very good and the character building of students can be done through education at the boarding school. Recommendations that can be suggested are to strengthen adab development, such as: ethics training, exemplary management, utilization of extracurricular activities that are more creative and character-oriented.